The Effect of Game – Like Exercises on the Development of Some Physical Abilities and Fundamental skills In Futsal - Ali, Hiba; Qasim, Sabah (Journal of Physical Education, 2023)
The research aimed at identifying the effect of special game – like exercises on some physical abilities and skills in futsal. The researchers used the experimental method on (20) female students. The researchers conducted physical abilities (long jump for explosive power) and hoping test (five hops for each leg for explosive power) skill tests (passing towards a small target 10m away, scoring test towards a divided goal). The main experiment lasted for two months with two training sessions per week making a total of (6) weeks and (12) training sessions. The main training part lasted for 30 – 40 minutes using game – like exercises with 80 – 90% intensity. The data was collected and treated using SPSS to conclude that there are significant statistical differences between pre and posttests results in physical abilities and fundamental skills understudy. In addition to that, the results showed the effect of game – like exercises on the subjects of the study. The researchers recommended using these exercises for training futsal female students as well as making similar studies on physical abilities and other skills and sports. Keywords: game – like exercises, futsal, explosive power, strength – speed, fundamental skills.